Morphological and behavioral evolutionary trajectories of ambrosia beetle-fungal mutualisms - Rudoy, Andrey (Universidade Estadual Paulista (Unesp), 2024)
Multiple bark and ambrosia beetle species, mainly from the subfamily Scolytinae, along with three and two species from the subfamily Platypodinae and the family Bostrichidae, respectively, were collected over one year (June 2023 – June 2024) in the campus of UNESP – Rio Claro, Brazil. Several symbiotic fungi including Rafaellea were obtained from these insects. Beetles were collected directly in tree galleries and by light trapping. The first method provided most of the Scolytinae and Bostrichidae species, and the second method provided the three recorded Platypodinae species and all fungal isolates (except for one isolate obtained in the first method). All fungal cultures were obtained from beetles belonging to the tribe Xyleborini (fungi-rearing group). Bark and ambrosia beetles were detected from ca. 10 species of trees, most from mango, jaca, and Ficus trees. Euwallacea spp. (Xyleborini) were found on all these trees. Although not an ambrosia beetle, Hypothemenus spp. seem to be a common group of bark beetles on campus, affecting dry twigs and dead branches of most trees, whereas Scolytinae were recorded near the bark. In contrast, species from Xyleborini and others borrow galleries in the xylem up to the core. Season differentiation of the groups and species seems uncertain but August-October and February-May seems to be the months with high numbers of species. This is the first report of these beetles for the UNESP campus, providing a first glimpse of the beetle and fungal associations in this location.
Trajetórias evolutivas morfológicas e comportamentais de mutualismos besouro-ambrosia-fúngico
Keywords: Besouro; Fungos; Evolução; Planta; Pragas; Beetle; Fungi; Evolution; Plant; Pests